Lincoln C. Andrews scrapbook. - Andrews, Lincoln C. (Lincoln Clarke), 1867-1950.
Scrapbook, mostly of newspaper clippings, concerning prohibition enforcement and Andrews' role in it.
Army officer.
Collection material in English.
Keywords: Prohibition; Army officers